An Overview of the Role of Mechanical Stretching in the Progression of Lung Cancer - Gong, Fengying; Yang, Yuchao; Wen, Liangtao; Wang, Congrong; Li, Jingjun; Dai, Jingxing (Frontiers in Cell and Developmental Biology, 2021)
Cells and tissues in the human body are subjected to mechanical forces of varying degrees, such as tension or pressure. During tumorigenesis, physical factors, especially mechanical factors, are involved in tumor development. As lung tissue is influenced by movements associated with breathing, it is constantly subjected to cyclical stretching and retraction; therefore, lung cancer cells and lung cancer-associated fibroblasts (CAFs) are constantly exposed to mechanical load. Thus, to better explore the mechanisms involved in lung cancer progression, it is necessary to consider factors involved in cell mechanics, which may provide a more comprehensive analysis of tumorigenesis. The purpose of this review is: 1) to provide an overview of the anatomy and tissue characteristics of the lung and the presence of mechanical stimulation; 2) to summarize the role of mechanical stretching in the progression of lung cancer; and 3) to describe the relationship between mechanical stretching and the lung cancer microenvironment, especially CAFs.